A goodness-of-fit test for a polynomial errors-in-variables model - Cheng, C.-L.; Kukush, A.G. (Український математичний журнал, 2004)
Polynomial regression models with errors in variables are considered. A goodness-of-fit test is constructed, which is based on an adjusted least-squares estimator and modifies the test introduced by Zhu et al. for a linear structural model with normal distributions. In the present paper, the distributions of errors are not necessarily normal. The proposed test is based on residuals, and it is asymptotically chi-squared under null hypothesis. We discuss the power of the test and the choice of an exponent in the exponential weight function involved in test statistics. Побудовано процедуру перевірки адекватності поліноміальної регресійпої моделі з похибками у змінних, що грунтується на адаптивній оцінці найменших квадратів і є модифікацією процедури, запропонованої в роботі Жу та іп. для перевірки адекватності лінійної структурної моделі з гауссовими похибками. У даній роботі не вимагається, щоб розподіл похибок був гауссовим. Запропонована процедура базується па залишкових членах і характеризується асимптотичним хі-квадрат розподілом при нульовій гіпотезі. Вивчено потужність процедури та питання про вибір показника експоненціальної вагової функції, яка використовується в процедурі.